Differences in classroom motivational climate: causes, effects and implications for teacher education. A multilevel study - Alonso-Tapia, Jesús; Ruiz, Miguel Ángel; Huertas, Juan Antonio (Anales de Psicología / Annals of Psychology, 2020)
Research on classroom motivational climate (CMC) has shown significant differences between classrooms in CMC. However, it is not known whether teachers’ motivational knowledge, and goals and expectancies related to their students contribute to such differences, and consequently, on the effects of CMC on students. For answering this question, a multilevel model of the relationships among a) teachers’ knowledge and motivational characteristics, b) students’ goals and expectancies (SGE), c) perceived CMC, and d) students’ attribution of perceived motivational improvement to teachers (APMIT) was tested using structural equation methods. A total of 2.223 Secondary and High-School students and their 95 teachers participated in the study. Results showed that teachers’ motivational quality (TMQ) has a significant indirect effect on differences between classrooms in CMC, and on the students’ attribution of perceived improvement in motivational variables to teachers, but also that teachers’ characteristics differ in their contribution to TMQ, and so, to CMC.